2019
DOI: 10.1002/ajh.25507
|View full text |Cite
|
Sign up to set email alerts
|

Imaging and bone marrow assessments improve minimal residual disease prediction in multiple myeloma

Abstract: The value of minimal residual disease (MRD) status by bone marrow and imaging analysis as independent prognostic factors has been well established in multiple myeloma (MM). Nevertheless data about their potential complementarity for a more accurate assessment are limited. With this aim, we retrospectively analyzed the prediction of outcome with the combination of PET‐CT and MRD, assessed by multiparameter flow cytometry (MFC) in 103 patients with newly diagnosed MM. We confirmed the benefit in terms of progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 58 publications
2
26
0
Order By: Relevance
“…Most recently, a retrospective study analyzed the prediction of outcome with the combination of 18 F-FDG PET/CT and MRD, assessed by MFC, in 103 patients with newly diagnosed MM. Apart from confirming the benefit-in terms of PFS-linked to the achievement of negativity by MFC and 18 F-FDG PET/CT individually, the authors showed that the combination of negativity by both techniques conferred significantly higher PFS than each technique alone, also supporting the potential complementarity between PET/CT and MFC in MRD detection [31].…”
Section: The Value Of 18 F-fdg Pet/ct In Minimal Residual Disease (Mrmentioning
confidence: 82%
“…Most recently, a retrospective study analyzed the prediction of outcome with the combination of 18 F-FDG PET/CT and MRD, assessed by MFC, in 103 patients with newly diagnosed MM. Apart from confirming the benefit-in terms of PFS-linked to the achievement of negativity by MFC and 18 F-FDG PET/CT individually, the authors showed that the combination of negativity by both techniques conferred significantly higher PFS than each technique alone, also supporting the potential complementarity between PET/CT and MFC in MRD detection [31].…”
Section: The Value Of 18 F-fdg Pet/ct In Minimal Residual Disease (Mrmentioning
confidence: 82%
“…[29][30][31] Of interest, according to the multivariable analysis, the prognostic value of disease response determined by MRD assessment (MFC or NGS) and imaging techniques (PET-CT) remains more predictive than the type of induction treatment administered or other conventional risk factors, as has been proposed in previous studies supporting the complementarity of both assessments. 16,32,33 In fact, prolonged therapy with lenalidomide achieved PET-CT negativity in more than 50% of patients who had pathological FDG uptake before maintenance, with those patients with persistent active lesions in PET-CT having an unfavorable prognosis. Nevertheless, the reduced number of patients with active disease in the initial PET-CT limited the possibility of performing a comprehensive analysis on its correlation with MRD results, in accordance with the findings of the aforementioned studies.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Disease assessment by imaging was conducted in some patients (n 5 119) with 18 F-fluorodeoxyglucose (FDG) positron emission tomography-computed tomography (PET-CT), according to previously described procedures. 16 The induction schemes before maintenance were heterogeneous (Table 1), and 83.5% of the patients (n 5 116) received ASCT. Maintenance treatment was performed with oral lenalidomide once daily on days 1 to 21 of repeated 28-day cycles.…”
Section: Methods Patientsmentioning
confidence: 99%
“…Different studies have evaluated the complementary role of PET/CT to existing methods such as bone marrow techniques, multiparameter flow cytometry (MFC) and next-generation sequencing (NGS). They reported higher OS in MRD-/PET-or MRD+/ PET-patients (4-year OS 94.2 and 100 % respectively) compared to PET+ patients (4-year OS 73.8%) [45].…”
Section: Conflict Of Interestmentioning
confidence: 95%